Pengaruh Konten Media Sosial dan Influencer Marketing terhadap Keputusan Pembelian Konsumen pada Followers Instagram Alito Sportwear - Sri Wahyuni; Mutya Paramita Pratita (Pusat Riset dan Inovasi Nasional, 2025)
In today’s increasingly competitive digital era, social media plays a strategic role in shaping brand image as well as influencing consumer purchasing decisions. Instagram, as one of the most popular visual platforms, has been widely utilized by fashion companies, including Alito Sportwear, to expand their marketing reach. This study aims to examine the effect of social media content and influencer marketing on consumer purchasing decisions among followers of Alito Sportwear’s official Instagram account. The research employed a descriptive quantitative method using a survey of 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression, following validity and reliability tests which confirmed that the research instruments were both valid and reliable. The findings indicate that both social media content and influencer marketing have a significant impact on consumer purchasing decisions. The coefficient of determination (R²) of 0.260 suggests that 26% of the variation in purchasing decisions can be explained by these two variables, while the remaining percentage is influenced by other factors beyond the scope of this study. These results highlight the importance of designing creative, relevant, and consistent content, as well as collaborating with credible influencers, to enhance consumer buying interest. Practically, the study provides insights for Alito Sportwear and other fashion businesses to optimize social media as an effective and competitive marketing tool.